PEMANFAATAN LIMBAH JERAMI PADI SEBAGAI PAKAN TERNAK ALTERNATIF DI DESA FAJAR BARU - Teguh Rafian; Ali Husni; Muhtarudin Muhtarudin; Akhmad Dakhlan; Dian Kurniawati (Jurnal Media Pengabdian Kepada Masyarakat, 2023)
Fajar Baru Farmer Group is also faced with the problem of less effective and efficient maintenance management, namely feeding that does not meet the needs and nutritional balance. It is necessary to carry out feeding management that suits the needs and nutritional balance of livestock. This is to create an independent and sustainable Fajar Baru Farmer Group in the cultivation of superior seeds in South Lampung. This community service activity uses two methods, namely presentation and demonstration. The community service was held on Saturday, August 5, 2023, at the Fajar Baru Village Livestock Group Chairman's house at 10.00 WIB until completion which was attended by 33 Fajar Baru Village farmers. First, the speaker gave a presentation on the nutritional needs of goats and sheep, what substances and nutrients are needed by goats and sheep during life and breeding, what feeds can be used, and what alternative feeds can be developed at the service location. Furthermore, a demonstration of making ammoniation of rice straw waste which is widely available at the service location was carried out. The service activity went smoothly and received a good response with a request to return to conduct counseling there.  Keywords: Ammoniation, Goat, Lampung, Sheep, Urea.